Osteotomy Site Grafting in Bilateral Sagittal Split Surgery With Bioactive Glass S53P4 for Skeletal Stability. Issue 7 (October 2017) - Stoor, Patricia; Apajalahti, Satu
Abstract : Abstract: In orthognathic surgery, the aim of the treatment is to achieve a good occlusion and a satisfying aesthetic outcome. In large mandibular advancements insufficient healing at the mandibular inferior border may lead to loss of support for the overlaying tissue at the osteotomy site. Augmentation can be performed to improve stability, bone regeneration, and the aesthetic outcome. The purpose of this prospective clinical study was to evaluate the use of a novel material for this indication; granules of the antibacterial, osteoconductive, and slowly resorbing bioactive glass S53P4 as filling material in large mandibular advancement in bilateral sagittal split osteotomies. The authors treated 25 patients who underwent bilateral sagittal split osteotomies due to class II dentoskeletal deformities. The mandibular osteotomy site defects (8–15 mm) were augmented with bioactive glass S53P4. The average clinical follow-up was 33 months and the average radiological follow-up with cone beam computerized tomography was 24 months. The clinical and radiological results were good with regard to healing, bone regeneration, and stability of the osteotomy sites. The recontouring of the inferior mandibular border provided a good soft tissue support followed by an excellent aesthetic outcome in 96% of the osteotomy sites. The occlusion was stable in 88% of the patients. The authors' results show that bioactive glass S53P4 is a safe grafting material for osteotomy site defects in significant mandibular advancements with reliable bone regeneration, providing long-term stability at the osteotomy site and at the inferior mandibular border.